Use of Kahoot! and Jamboard for the realization and organization of creative school activities during the COVID-19 pandemic - Salas-Rueda, Ricardo-Adán; Eslava-Cervantes, Ana-Libia; Alvarado-Zamorano, Clara (Creativity Studies, 2023)
This mixed study analyzes the students’ perception about the use of Kahoot! and Jamboard in the teaching–learning process about the English language during the COVID-19 pandemic through data science. Kahoot! is a web tool that facilitates and promotes the participation between the educator and students through the realization of digital games and Jamboard is a virtual wall that allows the active role through the dissemination of information and exchange of ideas. The participants are 30 students of Design and Visual Communication who took the English Language course in the distance modality at the National Autonomous University of Mexico, Mexico, during the 2020 school year. The results of the machine learning technique indicate that the realization of digital games in Kahoot! and the dissemination and exchange of information in Jamboard positively influence the motivation, assimilation of knowledge and participation of the students during the Verbs Unit. Data science identified 6 predictive models on the use of these technological tools in the educational process about the English language through the decision tree technique. Finally, educators have the opportunity to create new virtual spaces and promote the active role of the students by incorporating Kahoot! and Jamboard in the school activities during the COVID-19 pandemic.